Bluebirds and their survival - Davis, Wayne Harry, 1930- (University Press of Kentucky, 1995)
A fascinating guide which tells you what you need to know to bring more bluebirds into your life In this detailed how-to book, bluebird expert Wayne H. Davis tells how to attract and care for this beautiful and gentle bird and offers solutions to the most common bluebird problems. Since bluebirds are almost entirely dependent on people for providing nesting sites, the book contains plans for erecting a structure that will attract bluebirds to a safe habitat. Instructions for building and maintaining a ""bluebirds trail, "" complete with drawings of various bluebirds houses and guards against pr